Telemedicine: An IoT based Remote Healthcare System - M. Abdellatif, Mohammad; Mohamed, Walaa (International Journal of Online and Biomedical Engineering (iJOE), 2020)
This paper proposes a remote healthcare system which is referred to as Telemedicine. Telemedicine is a platform that estableshes a connection between the patient and the doctor. This platform belongs to the internet of medical things (IoMT) by enabling multiple medical sensors to connect to a server either using multiple communication technologies such as Wi-Fi, Bluetooth or GSM technologies. The system collects data from several sensors and sends them using one of the aforementioned technologies using an Arduino Board, while the interface is made with matlab and C#. Additionally, a comparative study between the three communications technologies used to connect the medical sensors to the server is investigated. And a recommendation of the best suited technology is provided with regard to the nature of the application itself.